Physical space, culture and organisational creativity – a longitudinal study - Tomi J. Kallio; Kirsi-Mari Kallio; Annika Johanna Blomberg (Emerald Group Publishing Limited, 2022)
Purpose – The purpose of this study is to explore the potential positive effects of the design of aphysical organisational environment on the emergence of an organisational culture conducive to organisational creativity.
Design/methodology/approach – The study is based on an in-depth, longitudinal case study, the aim being to enhance understanding of how a change in physical space, including location, spatial organisation and architectonic details, supports cultural change.
Findings – It is suggested that physical space plays an implicit yet significant role in theemergence of a culture conducive to organisational creativity. It appears from the case analysis that there are three aspects of culture in particular, equality, openness and collectivity, that may be positively affected by the design of an organisation’s physical environment.
Practical implications – The careful choice, planning and design of an organisation’s physicallocation, layout and style can advance the appearance of an organisational culture conducive to creativity.
Originality/value – The paper describes a longitudinal study comparing a case organisationbefore and after a change in its physical environment. The longitudinal data illustrates how a change in the spatial environment contributes to the emergence of a culture conducive to organisational creativity.